Mapping the advancements in forest soil arthropod research: A bibliometric analysis from 1960 to 2024 - Deepak Kumar Mahanta; Tanmaya Kumar Bhoi; Sharat Kothari (Soil Advances)
Forest soil arthropods play a vital role in sustaining soil health, biodiversity, and ecosystem functionality. This bibliometric analysis explores the development of forest soil arthropod research from 1960 to 2024, analyzing 2809 documents from the Scopus database using VOSviewer, Bibliometrix, and Biblioshiny in R. Results show a sharp rise in publications since the 1980s, peaking in 2021 with 152 articles. Insects dominate the field, comprising about 64 % of studies, especially beetles, springtails, and ants, due to their roles in decomposition, nutrient cycling, and bioindication. Arachnids, myriapods, and crustaceans are less studied, revealing notable research gaps. Thematic trends have shifted from taxonomy-based research to ecosystem service-oriented studies, with bioindication (61 %) and decomposition (27 %) emerging as key themes. Recent studies employ advanced tools like DNA metabarcoding and remote sensing, enabling a more precise quantification of species abundance and genetic diversity in soil ecosystems. Emerging topics include climate change, biological control, and functional trait analysis. Keyword analysis reveals a strong focus on biodiversity, soil health, and applied ecological themes, with a rising interest in ecosystem resilience. Global collaboration is robust, especially among countries with temperate and subtropical forests. However, research in tropical and subtropical dry forests remains limited, suggesting spatial and ecological gaps. The field reflects an interdisciplinary approach, linking agroecology, urban ecology, toxicology, and conservation. Expanding research on overlooked taxa and ecosystems is essential for promoting soil biodiversity and sustainable forest management.